2005
DOI: 10.1208/aapsj070240
|View full text |Cite
|
Sign up to set email alerts
|

Modeling and simulation of adherence: Approaches and applications in therapeutics

Abstract: Partial adherence with a prescribed or randomly assigned dose gives rise to unintended variability in actual drug exposure in clinical practice and during clinical trials. There are tremendous costs associated with incomplete and/or improper drug intake-to both individual patients and society as a whole. Methodology for quantifying the relation between adherence, exposure and drug response is an area of active research. Modeling and statistical approaches have been useful in evaluating the impact of adherence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 100 publications
0
30
0
Order By: Relevance
“…We found that the 43% of acne patients that did not adhere completely to treatment had worst final objective severity index scores. This non-adherence rate is in the range of patient non-adherence in dermatology (34–45%) [5], although it is well known that self-reported measurements tend to overestimate adherence [6]. In fact, when asked in a non-medical environment, 70% of acne patients said they adhered closely to the treatment [16], in contrast to the 57% when asked by the dermatologist.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We found that the 43% of acne patients that did not adhere completely to treatment had worst final objective severity index scores. This non-adherence rate is in the range of patient non-adherence in dermatology (34–45%) [5], although it is well known that self-reported measurements tend to overestimate adherence [6]. In fact, when asked in a non-medical environment, 70% of acne patients said they adhered closely to the treatment [16], in contrast to the 57% when asked by the dermatologist.…”
Section: Discussionmentioning
confidence: 99%
“…In dermatology, the rate of adherence to treatment varies between 55 and 66%, being lower for topical treatments [5]. Several models have shown that interventions that improve adherence to treatment increase the quality of life of patients [6]. One area that has not been examined thoroughly is the influence of the person’s quality of life upon adherence to treatment [7].…”
Section: Introductionmentioning
confidence: 99%
“…The indirect method of patient self-reporting is frequently used and is more inexpensive and patient friendly than many other strategies, such as the Medication Event Monitoring Systems, pill counts, or such direct methods as determination of drug concentrations in body fluids. [13][14][15] Because patients often overstate their adherence, results gained by self-reporting tend to overestimate adherence. 16 Yet, this bias can be somewhat reduced by stressing the anonymity of the data and by using questionnaires rather than direct interviews.…”
Section: ■■ Methods Patients and Study Designmentioning
confidence: 99%
“…Emulating this is exceedingly difficult but certainly not impossible. Significant strategies have been proposed, [130][131][132][133] including the concept of 'forgiving' drugs and tools for nonadherence calibration.…”
Section: Pharmacokineticsmentioning
confidence: 99%